2019
DOI: 10.1021/acsapm.9b00413
|View full text |Cite
|
Sign up to set email alerts
|

Development of l-Lysine Based Biodegradable Polyurethanes and Their Dual-Responsive Amphiphilic Nanocarriers for Drug Delivery to Cancer Cells

Abstract: The present investigation reports the development of new classes of l-lysine based polyurethanes by a solvent and isocyanate free melt transurethane polycondensation approach. New enzyme and thermo-dual responsive amphiphilic polyurethane nanocarriers were developed for the delivery of drugs both at the intracellular level and at cancer tissue temperature. Multifunctional l-lysine monomers were tailor-made by suitably converting the amine functionalities into urethanes (or carbamates) while masking the carboxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 71 publications
0
50
0
Order By: Relevance
“…All the in vitro studies showed effective drug release in the presence of enzyme at a temperature of 42 • C, which indicated the dual responsive characteristics of the nanoparticles. Overall, the utilization of L-lysine polyurethanes as a dual sensitive drug delivery system for delivering anticancer drugs could be a useful tool for cancer treatment (Joshi et al, 2019). Another study used polyurethanes containing DOX and camptothecin (CPT).…”
Section: Enzyme-responsive Systemsmentioning
confidence: 99%
“…All the in vitro studies showed effective drug release in the presence of enzyme at a temperature of 42 • C, which indicated the dual responsive characteristics of the nanoparticles. Overall, the utilization of L-lysine polyurethanes as a dual sensitive drug delivery system for delivering anticancer drugs could be a useful tool for cancer treatment (Joshi et al, 2019). Another study used polyurethanes containing DOX and camptothecin (CPT).…”
Section: Enzyme-responsive Systemsmentioning
confidence: 99%
“…Then, esterase enzyme was intracellularly acting to release the drug into the cancer cells. The same dual-responsive method was recently developed with a close approach [ 276 ].
Fig.
…”
Section: Biobased Pu For Biomedical Applicationsmentioning
confidence: 99%
“…PEG sidearm and polyurethane backbone assisted the polymers to self‐assemble into the core−shell nano assemblies, which exhibited unique thermoresponsiveness, which upon the extracellular trigger, leads to disassembly of nanocarriers. Further, the aliphatic urethane linkages in the amphiphilic aliphatic polyurethane backbone underwent lysosomal enzymatic degradation to deliver DOX in the tumor cells . Table summarizes the important thermoresponsive nanocarrier formulations.…”
Section: Nanocarriersmentioning
confidence: 99%
“…DOX and interferon (IFN ) 100 nm -Pluronic F127 [412] 3. DOX 180 nm 41−43 Amphiphilic Polyurethanes [417] 4. PTX, DOX 190-230 nm 34.8 PNIPAAm [407] 5.…”
Section: Thermo-responsive Nanocarriersmentioning
confidence: 99%
See 1 more Smart Citation